2014
DOI: 10.20333/25000136-2014-1-12-19
|View full text |Cite
|
Sign up to set email alerts
|

Markers of Systemic Inflammation and Endothelial Dysfunction in Patients With Chronic Obstructive Pulmonary Disease

Abstract: ГБОУ ВПО Красноярский государственный медицинский университет имени проф. В. Ф. Войно-Ясенецкого Министерства здравоохранения РФ, ректор-д. м. н., проф. И. П. Артюхов; кафедра внутренних болезней № 2 с курсом ПО, зав.-д. м. н., проф. И. В. Демко. p%'>,%. Результатами многочисленных исследований доказано влияние системного воспаления на формирование дисфункции эндотелия у больных ХОБЛ. В представленном обзоре показано, что в этом процессе активное участие принимают цитокины, молекулы межклеточной адгезии, белки… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
2
0
2

Year Published

2015
2015
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 33 publications
(2 reference statements)
0
2
0
2
Order By: Relevance
“…Проте існує багато суперечливих досліджень щодо вираження запального процесу залежно від стадії ХОЗЛ. За даними одних дослідників існує прямий зв'язок між стадією ХОЗЛ та ступенем системного запалення [8,10,11]. Спостерігається збільшення рівня IL1β, IL2, IL6, IL8 та СРБ пропорційно зростанню тяжкості ХОЗЛ, що пояснюється більш вираженою антигенною стимуляцією при тяжкому перебігу хвороби.…”
Section: вступunclassified
See 1 more Smart Citation
“…Проте існує багато суперечливих досліджень щодо вираження запального процесу залежно від стадії ХОЗЛ. За даними одних дослідників існує прямий зв'язок між стадією ХОЗЛ та ступенем системного запалення [8,10,11]. Спостерігається збільшення рівня IL1β, IL2, IL6, IL8 та СРБ пропорційно зростанню тяжкості ХОЗЛ, що пояснюється більш вираженою антигенною стимуляцією при тяжкому перебігу хвороби.…”
Section: вступunclassified
“…Спостерігається збільшення рівня IL1β, IL2, IL6, IL8 та СРБ пропорційно зростанню тяжкості ХОЗЛ, що пояснюється більш вираженою антигенною стимуляцією при тяжкому перебігу хвороби. Водночас, у роботах інших авторів показано, що при 4 стадії ХОЗЛ спостерігаються найменші показники IL [11][12][13]. При вивченні концентрації СРБ у пацієнтів із різними стадіями ХОЗЛ було виявлено найбільші значення при 1 та 2 стадіях, тоді як у хворих на 3 та 4 стадіях хвороби спостерігались практично нормальні величини [14,15].…”
Section: вступunclassified
“…Cardiovascular and respiratory pathological conditions also frequently coexist in modern clinical practice as they share the same risk factors and pathophysiologic pathways which in turn influence treatment choices (Global Initiative for Chronic Obstructive Lung Disease, 2013) [1]. Data obtained by Caroli and Rebrov [2] demonstrated that 61.8% of COPD patients experienced concurrent cardiovascular problems. Arterial hypertension occurred among those patients at the frequency rate ranging from 6.8 to 76.3% with the mean value 34.3%.…”
Section: Introductionmentioning
confidence: 99%
“…As a result of vasodilation, these medications improve pulmonary hemodynamics and therefore the right heart function [1,14]. Calcium channel blockers preserve the target organs by preventing or delaying vascular remodelling thus reducing arterial stiffness and ultimately improving endothelial vasodilation [2,7]. Amlodipine is the most clinically tested calcium channel blocker.…”
Section: Introductionmentioning
confidence: 99%